REORGANIZATION OF THE WORK PROCESS IN PRIMARY HEALTH CARE IN COPING WITH COVID-19 - Arnaldo, Juliana Gabrielle Santos; Radovanovic, Cremilde Aparecida Trindade; Magnabosco, Gabriela Tavares; Salci, Maria Aparecida; Galdino, Maria José Quina; Martins, Mayara Almeida; Zulin, Aline (Cogitare Enfermagem, 2023)
Objective: to assess the work process of Primary Health Care professionals in coping with COVID-19. Method: a qualitative study that used the health work process as conceptual basis and qualitative research as methodological framework. The collection procedure was carried out with 23 health professionals from July to September 2021, in the basic health units from a municipality in northwestern Paraná, Brazil. For the analysis, the data were organized by means of the MAXQDA software, and each data segment was organized according to the meanings. Results: two categories emerged, namely: Difficulties faced in reorganization of the ambience, programmatic activities and staffing of Primary Health Care professionals; and Organization of the care flow for users with COVID-19 in Primary Health Care. Conclusion: this study reinforces the indispensability of assessing the work process for health care improvement, especially in conditions of a public health emergency.